THE INFLUENCE OF WORK DISCIPLINE, MOTIVATION AND COMPETENCE ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT THE NATIONAL NARCOTICS AGENCY (BNN) LANGKAT REGENCY - Sri Wahyuni; Yohny Anwar (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of work discipline, motivation, and competence on employee performance with job satisfaction as an intervening variable at the National Narcotics Agency (BNN) of Langkat Regency. The independent variables in this study are work discipline, motivation, and competence; the dependent variable is employee performance; while the intervening variable is job satisfaction. This study uses a quantitative method with the Partial Least Squares – Structural Equation Modeling (PLS-SEM) approach through the SmartPLS application. The research sample was 39 respondents selected using a purposive sampling technique. The research instrument was a questionnaire with a Likert scale. Data analysis was carried out through evaluation of the outer model (validity and reliability) and the inner model (direct and indirect hypothesis testing). The results showed that: Work Discipline (X1) has a positive effect on Job Satisfaction (Z), with a path coefficient value (Original Sample column) of 0.173, and is significant, with a P-Value = 0.012 (Hypothesis Accepted). Work Discipline (X1) has a positive effect on Employee Performance (Y), with a path coefficient value (Original Sample column) of 0.235, with P-Value = 0.002 (Hypothesis Accepted). Job Satisfaction (Z) has a positive effect on Employee Performance (Y), with a path coefficient value (Original Sample column) of 0.942, with P-Value = 0.000 (Hypothesis Accepted). Competence (X3) has a positive effect on Job Satisfaction (Z), with a path coefficient value (Original Sample column) of 0.466, with P-Value = 0.000 (Hypothesis Accepted). Competence (X3) has a positive effect on Employee Performance (Y), with a path coefficient value (Original Sample column) of 0.472 with P-Value = 0.000 (Hypothesis Accepted). Motivation (X2) has a positive effect on Job Satisfaction (Z), with a path coefficient value (Original Sample column) of 0.502, with a P-Value = 0.000 (Hypothesis Accepted). Motivation (X2) has a positive effect on Employee Performance (Y), with a path coefficient value (Original Sample column) of 0.458, with a P-Value = 0.000 (Hypothesis Accepted). Employee Performance (Y) significantly mediates the relationship between Work Discipline (X1) and Job Satisfaction (Z), with a P-Value = 0.017 < 0.05 (Mediation Hypothesis Accepted). Employee Performance (Y) significantly mediates the relationship between Competence (X3) and Job Satisfaction (Z), with a P-Value = 0.000 < 0.05 (Mediation Hypothesis Accepted). Employee Performance (Y) significantly mediates the relationship between Motivation (X2) and Job Satisfaction (Z), with P-Value = 0.000 < 0.05 (Mediation Hypothesis Accepted). The implication of this study is the need for the management of the Langkat Regency BNN to continue to improve work discipline, work motivation, and employee competence, as well as create a work environment that supports job satisfaction, so that employee performance can be improved sustainably.